Het luitboek van Thysius: Facsimile-editie van Leiden, Bibliotheca Thysiana 1666 - Smout, Adriaan; Grijp, Louis Peter 1954-2016; Groot, Simon; Robinson, John H.; Burgers, Jan W. J. (Leiden Utrecht KVNM Nederlandse Luitvereniging, 2009)
The Thysius Lute Book is the largest source of handwritten lute music in the world. The manuscript, written in French tablature, was compiled around 1600 by the colorful preacher Adriaen Smout (1580 1646). After Smout's death, the manuscript was purchased at an auction of his household effects by Leiden librarian and book collector Johannes Thysius (1622 1651). The lute book, as well as Thysius' library, known as the Bibliotheca Thysiana, are still intact and on display in Leiden. The manuscript consists of more than 800 pages of music for 5/6/7-chord lute. The music originates from various parts of Europe and includes chanson and madrigal intervolutions, dance arrangements, fantasies and songs. The new NLV/KVNM edition consists of three hardcover volumes, collected in a stylish slipcase. The first volume, written and compiled by Jan Burgers, Louis Grijp, Simon Groot and John Robinson, provides a thorough introduction to the history and background of the Thysius Lute Book, as well as a comprehensive list of concordances. The remaining two volumes are facsimiles of the manuscript itself. (Translated with DeepL.com)
Band 1: inleiding en concordanties -- Band 2: Facsimile folio's 1-233 -- Band 3: facsimile folio's 233v-521v
Keywords: Thysius, Johannes -- 1622-1653; Bibliotheca Thysiana (Leiden, Netherlands); 17th Century (1601-1700); Lute; Manuscript; Tablature; Leiden (Netherlands)